Affective temperaments and neurocognitive functioning in bipolar disorder - Russo, Manuela; Mahon, Katie; Shanahan, Megan; Ramjas, Elizabeth; Solon, Carly; Braga, Raphael J.; Burdick, Katherine E. (Journal of affective disorders, 2014)
There is evidence that patients with bipolar disorder (BD) score higher on affective temperament ratings compared to healthy controls (HCs). Moreover, unaffected relatives demonstrate similar patterns as BD patients suggesting that such temperaments are related to the genetic risk for BD and may serve as endophenotypes for the disorder. It is unknown whether affective temperaments are associated with other core features of BD, such as impairments in neurocognition. This study examined the relationship between affective temperaments and neurocognition in patients with BD and in HCs. Temperaments were evaluated using the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego, Auto-questionnaire version (TEMPS-A) in 64 patients with BD and 109 HCs. Neurocognitive functioning was evaluated using the MATRICS Consensus Cognitive Battery (MCCB). Correlational analyses between temperaments and cognition were conducted in BD and HC subjects. Data suggest that affective temperaments and neurocognition are correlated. In BD higher ratings of cyclothymia and irritability were associated with better processing speed, working memory, reasoning and problem-solving. In the HC group, increased irritability was related to worse performance on measures of attention and social cognition. Lack of functional outcome measures to evaluate the impact of temperaments and cognition on psychosocial functioning. It would be useful to test these findings on unaffected relatives of BD patients. Cyclothymic and irritable temperaments are correlated with specific aspects of neurocognition in BD. This study is among the few exploring the dimensional relationship between temperaments and cognition in BD, and provides preliminary evidence for future studies investigating the neural and genetic mechanisms underlying the association between these variables.